Immunogenicity of the RTS, S/AS01 malaria vaccine and implications for duration of vaccine efficacy: secondary analysis of data from a phase 3 randomised controlled trial. Issue 12 (December 2015) - White, Michael T; Verity, Robert; Griffin, Jamie T; Asante, Kwaku Poku; Owusu-Agyei, Seth; Greenwood, Brian; Drakeley, Chris; Gesase, Samwel; Lusingu, John; Ansong, Daniel; Adjei, Samuel; Agbenyega, Tsiri; et al.
Summary: Background: The RTS, S/AS01 malaria vaccine targets the circumsporozoite protein, inducing antibodies associated with the prevention of Plasmodium falciparum infection. We assessed the association between anti-circumsporozoite antibody titres and the magnitude and duration of vaccine efficacy using data from a phase 3 trial done between 2009 and 2014. Methods: Using data from 8922 African children aged 5–17 months and 6537 African infants aged 6–12 weeks at first vaccination, we analysed the determinants of immunogenicity after RTS, S/AS01 vaccination with or without a booster dose. We assessed the association between the incidence of clinical malaria and anti-circumsporozoite antibody titres using a model of anti-circumsporozoite antibody dynamics and the natural acquisition of protective immunity over time. Findings: RTS, S/AS01-induced anti-circumsporozoite antibody titres were greater in children aged 5–17 months than in those aged 6–12 weeks. Pre-vaccination anti-circumsporozoite titres were associated with lower immunogenicity in children aged 6–12 weeks and higher immunogenicity in those aged 5–17 months. The immunogenicity of the booster dose was strongly associated with immunogenicity after primary vaccination. Anti-circumsporozoite titres wane according to a biphasic exponential distribution. In participants aged 5–17 months, the half-life of the short-lived component of the antibody response was 45 days (95% credible interval 42–48) and that of the long-lived component was 591 days (557–632). After primary vaccination 12% (11–13) of the response was estimated to be long-lived, rising to 30% (28–32%) after a booster dose. An anti-circumsporozoite antibody titre of 121 EU/mL (98–153) was estimated to prevent 50% of infections. Waning anti-circumsporozoite antibody titres predict the duration of efficacy against clinical malaria across different age categories and transmission intensities, and efficacy wanes more rapidly at higher transmission intensity. Interpretation: Anti-circumsporozoite antibody titres are a surrogate of protection for the magnitude and duration of RTS, S/AS01 efficacy, with or without a booster dose, providing a valuable surrogate of effectiveness for new RTS, S formulations in the age groups considered. Funding: UK Medical Research Council.